2018
DOI: 10.1002/adsc.201800462
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative [3+3] Annulation of Atropaldehyde Acetals with 1,3‐Bisnucleophiles: An Efficient Method of Constructing Six‐Membered Aromatic Rings, Including Salicylates and Carbazoles

Abstract: An oxidative [3+3] annulation of atropaldehyde acetals with various 1,3‐bisnucleophiles was developed using either N‐bromosuccinimide or copper(II) bromide as oxidizing reagent and Brønsted or Lewis acids as catalyst. The [3+3] annulations can be considered mechanistically as oxidizing reagent‐induced acid‐acid‐catalyzed domino reactions established through the concept of auto‐tandem catalysis. Alkyl acetoacetates, α‐(indol‐2‐yl)acetate, anilines, 1‐methyl‐1H‐pyrazol‐3‐amine, ethyl 5‐amino‐1H‐pyrazole‐3‐carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Recently, we have found that N -bromosuccinimide (NBS) can act as an oxidizing reagent to cooperate with a Lewis acid catalyst, and the established combined Lewis acid/NBS system can construct five- and six-membered aromatic rings . In this Article, we report a facile way to construct a six-and-five two-aromatic-ring fused heterocycle, namely, benzofuran, by using easily available chemicals, acrolein dimer and 1,3-dicarbonyl compounds, as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have found that N -bromosuccinimide (NBS) can act as an oxidizing reagent to cooperate with a Lewis acid catalyst, and the established combined Lewis acid/NBS system can construct five- and six-membered aromatic rings . In this Article, we report a facile way to construct a six-and-five two-aromatic-ring fused heterocycle, namely, benzofuran, by using easily available chemicals, acrolein dimer and 1,3-dicarbonyl compounds, as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Our group reported NBS‐assisted Al(OTf) 3 ‐catalyzed [3+3] annulation of atropaldehyde acetals with bisnucleophiles, which can construct aromatic rings with high efficiency (Scheme 4). [19] It was proposed that the reaction proceeded through acascade annulation/aromatization process. Likewise, NBS contributed a significant role in the last aromatization step, and shifted the equilibrium toward the right side.…”
Section: Oxidizing Component‐induced Reactionsmentioning
confidence: 99%
“…In the past five years, our group has focused on the reactivity exploration of atropaldehyde acetals and the establishment of cascade process based on atropaldehyde acetals, which acted as multipurpose precursors for various units to construct diverse privileged scaffolds (Scheme 1). [9c,d] For instance, atropaldehyde acetals were utilized as a pivotal C3 fragment to combine with different bisnucleophiles through oxidative [3+3] annulation in the presence of NBS, affording six‐membered aromatic rings, salicylates and carbazoles [9c] . Atropaldehyde acetals were recently demonstrated to be a masked C2 electrophile like a new type of “phenylacetyl or styryl surrogate”, due to the easy cleavage of the carbon‐carbon bond.…”
Section: Introductionmentioning
confidence: 99%